SERUM NICKEL LEVELS OF DIABETIC-PATIENTS AND HEALTHY CONTROLS BY AAS WITH A GRAPHITE-FURNACE - (:unkn) unknown (HUMANA PRESS INC, 1992)
In this study, serum nickel levels of diabetic patients and healthy controls were determined by AAS with a graphite furnace. The serum nickel concentrations were found to be 1.15 +/- 1.89 mug/L in healthy controls and 0.82 +/- 0.74 mug/L in diabetics. There was, however, no statistically significant difference between the two groups (p = 0.13). The relationship of nickel levels to diabetes type and duration, diabetic complications and treatment, sex, age, and heredity was investigated. However, again no significant differences were found, nor was there any correlation between serum nickel levels and blood sugar, HbA1c, fructoseamine, sialic acid levels, and age.
Keywords: DIABETES; SERUM, NICKEL LEVELS; ZN-SUPEROXIDE DISMUTASE; GLUCOSE; PLASMA; TRACE; RATS; GLYCATION; ELEMENTS; GLUCAGON; INSULIN; NI(II)